2018
DOI: 10.1186/s13287-018-0878-1
|View full text |Cite
|
Sign up to set email alerts
|

Systemically administered allogeneic mesenchymal stem cells do not aggravate the progression of precancerous lesions: a new biosafety insight

Abstract: BackgroundMesenchymal stem cells (MSCs) are a heterogeneous subset of stromal cells currently tested for multiple therapeutic purposes. Their potential to home into tumors, to secrete trophic/vasculogenic factors, and to suppress immune response raises questions regarding their biosafety. Our aim was to evaluate whether systemically administered allogeneic MSCs modify the natural progression of precancerous lesions and whether their putative effect depends on cancer stage and/or cell dose.MethodsOral squamous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Moreover, it has been shown that MSC can actually inhibit the progression of cancerous tumors. In hamsters with induced premalignant stages of squamous cell carcinoma of the mouth cavity, they decreased the progression of lesions (except for the largest doses) [117]. Less optimistic are the latest discoveries in the field of MSC immunogenicity.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been shown that MSC can actually inhibit the progression of cancerous tumors. In hamsters with induced premalignant stages of squamous cell carcinoma of the mouth cavity, they decreased the progression of lesions (except for the largest doses) [117]. Less optimistic are the latest discoveries in the field of MSC immunogenicity.…”
Section: Discussionmentioning
confidence: 99%
“…Samples were classified according to the revised criteria given by the World Health Organization (2005). Three independent observers performed histological analyses blind; one of them is a pathologist expert in oral diseases 57 , 58 .…”
Section: Methodsmentioning
confidence: 99%
“…Five representative optical sections by sample (n=6/group) were photographed using 60X magnification. The images obtained per field of each sample, were processed with the same conditions and the positive protein signal (pixels intensity) was analyzed and quantified using Fiji Image J software (NIH, USA) 56,57 .…”
Section: A-b)mentioning
confidence: 99%